Evaluasi Keterbatasan Modul Pencemaran Sampah dengan Argument Driven Inquiry (ADI) dalam Membentuk Perilaku Lingkungan - Diartika, Eka Imbia Agus; Sueb, Sueb; Al-Muhdhar, Mimien Henie Irawati (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the effectiveness and limitations of a waste pollution module based on the Argument Driven Inquiry (ADI) model in shaping environmental behavior among biology students. A nonrandomized control-group pretest–posttest design was employed involving three biology student classes at Universitas Negeri Malang: the experimental class (ADI module), positive control (ADI model), and negative control (PowerPoint presentation). Data were collected using an environmental behavior questionnaire covering indicators of pro-environmental activity, non-active public behavior, and household environmental behavior. ANCOVA analysis showed that although all classes experienced an increase in posttest scores, there was no statistically significant difference among the treatment groups (p > 0.05). This indicates that the ADI module was not significantly more effective than other teaching methods in improving environmental behavior. Limitations such as online learning constraints, lack of direct interaction, and technical challenges in module implementation contributed to this outcome. Nevertheless, the ADI module has potential as a contextual learning tool and is recommended for further development into a more practical and interactive digital format.